Complete genome sequence analysis of temperate Erwinia bacteriophages 49 and 59 - Zlatohurska, Maryna; Gorb, Tetiana; Romaniuk, Liudmyla; Korol, Natalia; Faidiuk, Yuliia; Kropinski, Andrew M.; Kushkina, Alla; Tovkach, Fedor (Journal of basic microbiology, 2019)
To date, a small number of temperate phages are known to infect members of the genus Erwinia. In this study, the genomes of temperate phages vB_EhrS_49 and vB_EhrS_59 infecting Erwinia horticola, the causative agent of beech black bacteriosis in Ukraine, were sequenced and annotated. Their genomes reveal no significant similarity to that of any previously reported viruses of Enterobacteriaceae. At the same time, phages 49 and 59 share extensive nucleotide sequence identity across the regions encoding head assembly, DNA packaging, and lysis. Despite significant homology between structural modules, the organization of distal tail morphogenesis genes is different. Furthermore, a number of putative morons and DNA methylases have been found in both phage genomes. Due to the revealed synteny as well as the structure of lysogeny module, phages 49 and 59 are suggested to be novel members of the lambdoid phage group. Conservative structural genes together with varying homology across the nonstructural region of the genomes make phages 49 and 59 highly promising objects for studying the genetic recombination and evolution of microbial viruses. The obtained data may as well be helpful for better understanding of relationships among Erwinia species.